Educação Física no ensino médio: um estudo de caso numa escola técnica - Benedetti, Augusto Pio (2008)
There is, on the Physical Education classes of the Colégio Técnico Industrial (CTISM), a history of growth of the number of students absence from the first to the third grade of Ensino Médio. The objective of this study consisted of identifying and analyzing the causes that lead students to progressively become less engaged on this subject and to become more absent from these classes. Thus, the reason why the third graders of CTISM were more absent from the Physical Education classes than the first-graders was the research question. This study was based on a qualitative research and the research method of case study in the line of research School and Political Practices Public. The participants were a total of seventeen (17) students, being nine (09) students who were on third grade in 2007 and eight (08) students who graduated in 2006 with an elevated rate of class absence. The instruments which were used consisted of an exploratory subject by the third graders as well as a semistructured interview. For the results analysis, the method of content analysis was utilized. From the interaction of the theoretic and empirical elements, two categories that sum up the research results emerged: a) social conditioners; b) physical education conception.